Incidence Of equine hoof derangements in Selangor and federal territory of Kuala Lumpur and Putrajaya, Malaysia - Zainal Abiddin, Nurul Syuhada; Fateh Mohamed, Bashir Ahmad (2012)
The study was carried out to investigate the various environmental conditions responsible for abnormal hoof conformity and lameness in horses from various establishments as the result of poor management. The hooves of the horses in five establishments in Selangor, Putrajaya and Kuala Lumpur were examined for abnormal hoof conditions ranging from thrush, soft sole, seedy toe, hoof crack, hoof ring, chip hoof and displaced coronet. The management and nutrition statuses were recorded via observation and personal communication. Fifty-three horses of different breeds and usage were selected and categorised as clinically healthy, actively working and shod. These horses comprised of 20 Thoroughbreds, 21 Arabs, 2 each of Anglo-Arabs, Warmbloods, Percherones, Andalusians and 1 each of Appaloosa, Crossbred, Stock Horse and Quarter Horse. Factors that were compared in relation to incidence of hoof derangements were breed, use of the horse, hoof pigmentation, management and nutrition. Hoof derangements were scored according to severity. Six types of hoof derangements recorded were chipped hoof, thrush, hoof ring, grass crack, horizontal crack and sand crack. The incidence rate for chipped hoof was the highest with 52 cases (53.52%). The lowest incidence rate recorded was sand crack where only one case was recorded (0.96%). Other hoof derangements were grass crack (41.74%), Thrush (40.20%), hoof ring (39.00%) and horizontal crack (3.37%). The high incidence of hoof derangements in this study was due to poor management and inappropriate nutrition. The study also showed that there is a relationship between use of horse and thrush and chipped hoof conditions.